Comparison of the Efficacy of Local Corticosteroid Injection and Physical Therapy on Pain Severity, Joint Range of Motion and Muscle Strength in Patients with Shoulder Impingement Syndrome Referred to Rasool-e-Akram Medical Center from April 2008 to September 2009 - Hosein Farahini; Ali Yeganeh; Mahsa Abdollahi; Morteza Nakhaei Amroodi (Medical Journal of The Islamic Republic of Iran, 2011)
Backgrounds: Subacromial impingement is a common cause of shoulder pain and many patients with this condition recover with conservative management. The most commonly used modalities of nonoperative treatment include activity modification, anti-inflammatory medication and subacromial injection of steroid and ultrasound and physical therapy programs. This study assessed the value of physiotherapy versus subacromial corticosteroid injection in patients with shoulder impingement syndrome (SIS). Methods: Seventy three patients with SIS enrolled in the study and treated through physiotherapy (n=37) and subacromial corticosteroid injection (n=36). Two follow-up sessions accomplished at the end of 4th week and 3rd month of treatment respectively. Results: Corticosteroid injection caused dramatic improvement in the painful state (p<0.0001) and sleep dysfunction score (p=0.039) in the first follow-up. However, physiotherapy showed significantly better results regarding patients’ pain score (p=0.016) and their shoulder join range of motions (p=0.017 and p=0.029 for the abduction and extension, respectively) in their second follow-up. Conclusion: Our study results showed that subacromial corticosteroid injection primarily resulted in more improvement in the impingement symptoms. However, with the long-term follow-up the results were better for the physiotherapy. These results suggest that patients should not undergo surgery before having conservative treatment.